Exploring the relationship between organizational politic and knowledge sharing in Brazilian modular consortium - Rodriguez, Indira Arias [UNESP]; Muniz, Jorge [UNESP]; Munyon, Timothy P. (IGI Global, 2021)
This research aimed to explore the relationship between employees’ perceptions of organizational politics (POPS) and their predisposition to involve in knowledge sharing (KS) behaviors at individuals and workgroups level in the Brazilian automotive Modular Consortium. The sample included 144 shop floor employees of Modular Consortium (six connected companies in assembly lines). The POPS-KS relationship was analyzed using different referents, seeking to understand how individuals and groups respond to the presence of organizational politics, and POPS and KS were tested in a Brazilian context, shedding new light on potential cultural influences impacting this relationship. The results evidenced that positive interpersonal communication can contribute to KS, and in turn, KS can counteract the negative impacts of POPS. There was a positive relationship between POPS-KS, indicating that POPS may have functional effects in facilitating KS of individuals and workgroups. Key findings and implications for future research were discussed.
Keywords: Knowledge Sharing of Group; Knowledge Sharing of Individuals; Modular Consortium; Perceptions of Organizational Politics; Shop Floor Workers